Analiza różnic w ocenie stresu i lęku przedstartowego z wykorzystaniem testów SCAT i CSAI-2d = Analysis of differences in the evaluation of pre-competition stress and anxiety using SCAT and CSAI-2d tests - Michał Adam Kosiński; Wojciech Aleksander Kosiński (Kazimierz Wielki University, 2016)
Kosiński Michał, Kosiński Wojciech. Analiza różnic w ocenie stresu i lęku przedstartowego z wykorzystaniem testów SCAT i CSAI-2d = Analysis of differences in the evaluation of pre-competition stress and anxiety using SCAT and CSAI-2d tests. Journal of Education, Health and Sport. 2016;6(12):53-61. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192192 http://ojs.ukw.edu.pl/index.php/johs/article/view/4029       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 02.12.2016.       Analiza różnic w ocenie stresu i lęku przedstartowego z wykorzystaniem testów SCAT i CSAI-2d Analysis of differences in the evaluation of pre-competition stress and anxiety using SCAT and CSAI-2d tests   Kosiński Michał1, Kosiński Wojciech2   MN/WF/6/2016,   1Akademia Wychowania Fizycznego i Sportu im. Jędrzeja Śniadeckiego w Gdańsku / Gdańsk University of Physical Education and Sport 2Gdański Uniwersytet Medyczny / Medical University of Gdańsk   Słowa kluczowe: sport, aktywność fizyczna, psychologia Key worlds: sport, physical activity, psychology     Streszczenie Głównym celem niniejszej pracy było porównanie wyniku badań lęku i stresu przedstartowego mierzonego za pomocą testów SCAT i CSAI-2d wśród pływaków i ratowników. Praca została napisana w oparciu o artykuł Competitive Anxiety in Lifesavers and Swimmers (Avramidou E., Avramidis S., Pollman R., 2007) zamieszczony w International Journal of Aquatic Research and Education z wykorzystania testu psychologicznego CSAI-2d oraz badania własne prowadzone przez autora z użyciem testu SCAT przeprowadzone w latach 2013-2015. Grupę docelową w obu badaniach stanowili zawodnicy rywalizujący w zawodach sportowych we wskazanych dyscyplinach. Ankiety SCAT były anonimowe. Ankietowani, w liczbie prawie 350, pochodzili z Polski, Czech, Niemiec i Belgii. Analiza wyników wykazała rozbieżności pomiędzy wynikami testu SCAT i testu CSAI-2d, co spowodowane mogło być małą liczebnością jednej z badanych grup (20 osób). W obu badaniach lęk przedstartowy został oceniony na podobnym poziomie.     Summary The main aim of this paper was to compare whether the level of perceived anxiety and pre-competition stress tested with SCAT and CSAI-2d among the athletes representing swimming and water rescue sports. The paper was based on article Competitive Anxiety in lifesavers and Swimmers (Avramidou E., Avramidis, S., Pollman R., 2007) printed in the International Journal of Aquatic Research and Education from the use of psychological test CSAI-2d and own research conducted by the author with SCAT test (all the work was carried out in 2013-2015). The target group consisted of athletes competing in a specific discipline. SCAT Surveys were anonymous. The respondents in the number of nearly 350, came from the Poland, Czech Republic, Germany and Belgium. Analysis of the results showed a discrepancy between the results of the CSAI-2d test and the SCAT test, which could be due to the small sample size of respondents group (20 athletes). In both studies, however, the level of anxiety has been evaluated at a similar level.